Abstract 4139542: Left or Bilateral Cardiac Sympathetic Denervation: Comparison of Antiarrhythmic Efficacy and Complications - Girvin, Zachary; Wright, Adam; Shoemaker, BEN; Bichell, David; Shah, Ashish; Kannankeril, Prince (Circulation (New York, N.Y.), 2024)
Background: Cardiac sympathetic denervation (CSD) is a well-established procedure to prevent ventricular arrhythmias in genetic and acquired arrhythmia syndromes. It is unknown whether initial bilateral (B) CSD or left (L) CSD, followed by right (R) CSD for breakthrough events is the better strategy. Aims: We compared the antiarrhythmic efficacy and complications of primary B vs L CSD at a single center where both are performed routinely. Methods: Patients who underwent CSD were retrospectively identified. At our center L CSD is performed in children while B CSD is performed in adults by operator preference. Demographic data, procedural indications, complications, and arrhythmia events (arrhythmic syncope, sudden cardiac arrest, appropriate shock) were collected. Arrhythmia events (AE) were compared before and after CSD in those with arrhythmia indications. Complications were compared in all subjects and in the subset with arrhythmia indications. Results: Between 2011 and 2023, 65 patients underwent 68 CSD procedures (39 B, 26 L, 3 R after initial L). As expected, BCSD patients were older [median 32 (IQR 21-48) years vs. 16 (6-38) years; P=0.002]. Overall complication rates were similar [BCSD 17/39 (44%) vs 12/29 (41%), P=0.85]; most were transient/minor. Complications that required intervention were rare (n=5) and only observed after BCSD. Forty CSD were for an arrythmia indication (18 B, 21 L, 1 R). AEs were reduced from a median of 3 (1-4) before CSD to 0 (0-1) after CSD (p<0.001). The reduction was similar for BCSD [3.5 (2-5) before vs 0 (0-0.25) after (p<0.001)] and L/R CSD [2 (1-4) before vs 0 (0-1) after (p=0.002)]. Only 1 LCSD had subsequent RCSD for an arrhythmia indication 4 years later due to breakthrough AEs: a severe long QT syndrome patient who ultimately required heart transplant. Complications that required intervention after CSD for an arrhythmia indication were seen in 4/18 BCSD and 0/22 L/R CSD (P=0.03). Conclusions: BCSD and LCSD are both highly effective in reducing arrhythmia events. Complication rates may be less frequent in unilateral CSD, although the observed difference may be due age differences in the two groups.